Faktor-Faktor Yang Berhubungan Dengan Kesiapan Perawat Dalam Melaksanakan Evidence-Based Practice (EBP): A Literature Review - Rahmayanti, Elifa Ihda; Kadar, Kusrini S; Saleh, Ariyanti (Jurnal Keperawatan, 2019)
Evidenced-based Practice (EBP) functions integrally in health services as an ideal problem-solving approach and it emphasizes on the application of the best research in making health care decisions. The ability of nurses to conduct EBP is strongly influenced by several factors. The aim of this study was to identify factors related to the readiness of nurses in the implementation of EBP. This study was a literature review using several articles related to the theme which taken from the database of electronic publications such as Pubmed, SAGE Journal, ProQuest, and Science Direct. The results of this study showed that there were 12 journals that meet with the the inclusion criteria. There were six journals described that attitudes and beliefs, knowledge and skills, workplace cultures, information needs, education levels, work experiences, and ages are the things that can determine the readiness of nurses in the application of EBP. Furthermore, five different journals showed that the challenges in the EBP implementation are workplace cultures and organizations, lack of human resources, lack of time, lack of internet access, lack of knowledge and skills and workload. Moreover, one journal concluded that the need for training and guidance for nurses to improve their knowledge and skills about EBP. In conclusion, knowledge and skills, attitudes and beliefs regarding EBP are the most important factors for nurses in implementing EBP. However, the main inhibitory factors of the EBP implementation are workplace cultures and organizations that are resistant to change.